Screening of Selected Medicinal Plants of Pokhara Valley for their Antimicrobial Activities - Tiwari, Birendra; Raut, Bechan (Journal of Natural History Museum, 2009)
The crude compounds from eight medicinal plants viz. Justicia adhatoda L., Solanum virginianum L., Artemisia indica Willd, Eclipta prostrata (L.) L., Cuscuta reflexa Roxb., Mentha arvensis L., Acorus calamus L. and Woodfordia fruticosa (L.)Kurz. claimed by Ayurvedya, traditional healers and other people in different diseases of microbial origin were extracted with water by percolation technique and solvent was completely removed by rotatory vacuum evaporator. The extracts were then tested for their antimicrobial activities at dilution of 5mg/ ml against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Salmonella paratyphi and Shigella dysenteriae. At this dilution, only the Cuscuta reflexa Roxb. has shown its susceptibility against all the tested micro-organisms. Key words: Medicinal plants; Antimicrobial activities; Micro-organisms; Health care system; Pokhara valley. Journal of Natural History Museum Vol. 24, 2009 Page: 16-20